Efficient modified cation exchange resin and preparation method thereof
By reinstalizing the cedic exchange resin and lignin, composite flocculant and modified activated carbon, prepare a high -efficiency modified cation exchange resin, which solves the problem of being easily contaminated and structural destruction during water treatment. Vertical adsorption, stability and durability of resin.
Patent Information
- Application Number
- CN202411786524.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-24
AI Technical Summary
Cationic exchange resins are easily contaminated by microorganisms during water treatment, resulting in the damage to the resin structure, loss of ion exchange function, and difficult to regenerate effectively.
By compounding the cation exchange resin with lignin, composite flocculant and modified activated carbon, a highly efficient modified cation exchange resin is prepared. Modified activated carbon improves adsorption performance and structural stability through hydroxylation and the introduction of graphene oxide; lignin and composite flocculants enhance the flocculation and regeneration capabilities of the resin.
Modified cation exchange resin shows good adsorption, stability and durability, can effectively resist the impact of water flow and mechanical stress, extend service life and improve regeneration capacity.
Smart Images

Figure BDA0005174191410000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cation exchange resins and relates to a high-efficiency modified cation exchange resin and a preparation method thereof. Background Art
[0002] Ion exchange resin is a network insoluble functional polymer material with ion exchange groups. The matrix of ion exchange resin mainly includes two categories: styrene and acrylic acid (ester), which are polymerized with cross-linking agent divinylbenzene to form a polymer with a network skeleton structure.
[0003] Ion exchange resin is a cross-linked polymer loaded with active groups, which has the functions of exchange, absorption and catalysis. Ion exchange resin is mainly used in water treatment, food, electricity, medicine and health, metallurgy and other fields.
[0004] Ion exchange resin is one of the common consumables in water treatment. Ion exchange resin can maintain efficient kinetic performance and high operating exchange capacity when used. When some aqueous solutions containing metal cations meet acidic groups such as cation exchange resins in water, metal ions will exchange with H ions on the ion exchange resin, so that the cations in the solution are transferred to the resin.
[0005] During the water purification process, cation exchange resins will adsorb microorganisms in the water, and these microorganisms will use some components in the resin as nutrients to reproduce, causing the water quality to be polluted and the structure of the resin to be destroyed, which in turn causes the ion exchange resin to lose its ion exchange function. Summary of the invention
[0006] The object of the present invention is to provide a highly efficient modified cation exchange resin and a preparation method thereof. The prepared cation exchange resin has good adsorption, stability and durability.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A high-efficiency modified cation exchange resin comprises the following components in parts by weight: 100-120 parts of cation exchange resin, 10-15 parts of lignin, 10-15 parts of composite flocculant and 10-15 parts of modified activated carbon.
[0009] The preparation process of the modified activated carbon is as follows:
[0010] S1.1, mixing activated carbon with a mixed solution of hydrogen peroxide and concentrated sulfuric acid, heating to 50-80°C and stirring for 24-48 hours, filtering after stirring, washing the obtained solid with deionized water and ethanol for 2-3 times, respectively, and drying at 95°C for 16-20 hours under vacuum conditions to obtain surface hydroxylated activated carbon, wherein the mass ratio of the activated carbon to the mixed solution of hydrogen peroxide-concentrated sulfuric acid is (1-3): (20-30);
[0011] S1.2, at room temperature, add activated carbon, tetrapropylammonium hydroxide and pure water into a reactor, stir at a speed of 350r / min for 3 to 5h, filter, wash with pure water, and dry in a drying oven at 75 to 85°C for 8 to 14h to obtain pretreated activated carbon;
[0012] S1.3. At 100-120°C, mix 20-30 parts of pretreated activated carbon, 20-30 parts of surface hydroxylated activated carbon and 60-80 parts of graphene oxide dispersion, stir at 300 r / min for 60-70 h, filter, dry at 85°C for 8-12 h, ball mill at 300 r / min for 4 h, and pass through a 200-mesh sieve to obtain modified activated carbon.
[0013] As a preferred technical solution of the present invention, the preparation process of the composite flocculant is as follows:
[0014] The lignin is dried in a drying oven at 70°C for 6 to 12 hours, and then ball-milled at a speed of 400 r / min for 1 to 3 hours by a ball mill, 30 to 40 parts of the ball-milled lignin, 50 to 70 parts by weight of polyacrylamide and 70 to 85 parts of pure water are mixed, and the mixture is heated to 80 to 95°C, stirred at this temperature for 1 to 2 hours, and dried at 85 to 90°C for 7 to 10 hours to obtain the composite flocculant.
[0015] As a preferred technical solution of the present invention, in step S1.1, the volume ratio of hydrogen peroxide to concentrated sulfuric acid in the mixed solution of hydrogen peroxide and concentrated sulfuric acid is 1:(3-5).
[0016] As a preferred technical solution of the present invention, in step S1.2, the mass ratio of the activated carbon, tetrapropylammonium hydroxide and pure water is 10:(1-3):70.
[0017] As a preferred technical solution of the present invention, in step S1.3, the mass concentration of the graphene oxide dispersion is 3-5%.
[0018] A method for preparing a highly efficient modified cation exchange resin comprises the following steps:
[0019] S1. Rinse the cation exchange resin with ethanol, place it in an acidic solution after drying, react at room temperature for 2 to 4 hours, wash it with deionized water until it is neutral, filter it, and dry it to obtain a pretreated cation exchange resin;
[0020] S2, adding the pretreated cation exchange resin, lignin, and composite flocculant to an organic solvent by weight, mixing and stirring evenly under heating conditions, filtering, and drying to obtain a modified cation exchange resin powder;
[0021] S3. Mix the modified cation exchange resin powder and the modified activated carbon, stir them evenly at a speed of 350 r / min, and granulate them to obtain the modified cation exchange resin.
[0022] As a preferred technical solution of the present invention, in step S1, the acidic solution is a hydrochloric acid or sulfuric acid solution with a molar concentration of 1 to 3 mol / L.
[0023] As a preferred technical solution of the present invention, in step S1, the mass ratio of the acidic solution to the cation exchange resin is 10:1.
[0024] As a preferred technical solution of the present invention, in step S2, the heating temperature is 35-40°C, the mixing speed is 300r / min, and the time is 3-5h.
[0025] As a preferred technical solution of the present invention, in step S2, the drying condition is drying at 50-60° C. for 6-8 hours.
[0026] The hydroxyl functional groups on the surface of hydroxylated activated carbon can significantly enhance its adsorption capacity for macromolecular organic matter. The presence of hydroxyl functional groups can form stronger interaction forces between activated carbon particles, thereby preventing them from agglomerating or precipitating in aqueous solutions. This improvement in stability helps the activated carbon maintain its excellent adsorption and catalytic properties during long-term use.
[0027] The activated carbon is pretreated with tetrapropylammonium hydroxide. Tetrapropylammonium hydroxide can separate tetrapropylammonium cations in water, which will physically adsorb to the surface of the activated carbon, change the charge distribution and functional group types on the surface of the activated carbon, and enrich the functional groups on the surface of the activated carbon. The pretreated activated carbon is mixed with hydroxylated activated carbon, and graphene oxide is added at the same time. The introduction of graphene oxide can optimize the pore structure of the activated carbon, making it more conducive to the diffusion and adsorption of substances, thereby increasing the adsorption rate. The hydroxyl functional groups on the surface of hydroxylated activated carbon also have excellent adsorption properties and can adsorb more water molecules and other polar substances. Graphene oxide has a two-dimensional structure and a high specific surface area, and can adsorb a large number of gas and liquid molecules. After the three are mixed, a composite material with a multi-level structure can be formed, thereby improving the overall adsorption performance, and can resist the impact of water flow and mechanical stress, thereby improving the stability and durability of the resin.
[0028] Lignin-modified polyacrylamide has a stronger flocculation ability, which can effectively condense suspended matter, colloidal substances, etc. in water into larger particles, thereby accelerating the sedimentation rate and improving water treatment efficiency. Adding a composite flocculant to the cation exchange resin can accelerate the coagulation and sedimentation of pollutants in the water, thereby shortening the treatment time of the cation exchange resin, which can not only improve the treatment efficiency, but also reduce the investment and operation cost of the equipment. At the same time, since the flocculant can remove most of the pollutants in the water, it can reduce the load of the cation exchange resin, extend its service life, reduce the regeneration frequency and the amount of regeneration agent. The addition of flocculants can reduce the scouring and wear of the cation exchange resin by suspended matter in the water, thereby protecting the physical structure and performance of the resin. By removing pollutants such as suspended matter and organic matter in the water, it can ensure that the exchange sites of the cation exchange resin will not be occupied by these impurities, thereby improving its exchange capacity and exchange efficiency.
[0029] During use, cation exchange resins will gradually become saturated and need to be regenerated to restore their exchange capacity. The addition of lignin can promote the regeneration process of the resin. On the one hand, lignin can act as a "buffer" to help the resin release adsorbed cations more easily during the regeneration process; on the other hand, lignin molecules contain a large number of functional groups such as hydroxyl and carboxyl, which help the resin release adsorbed cations during the regeneration process, thereby extending the overall service life of the resin.
[0030] Beneficial effects of the present invention:
[0031] In the present invention, a cation exchange resin, lignin, a composite flocculant and modified activated carbon are compounded to obtain a modified cation exchange resin. The modified cation exchange resin has good adsorption, high stability and good durability. DETAILED DESCRIPTION
[0032] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.
[0033] Example 1
[0034] Preparation of modified activated carbon:
[0035] S1.1, mixing activated carbon with a mixed solution of hydrogen peroxide and concentrated sulfuric acid, heating to 50°C and stirring for 24 hours, filtering after the stirring, washing the obtained solid with deionized water and ethanol twice respectively, and drying at 95°C for 16 hours under vacuum conditions to obtain surface hydroxylated activated carbon, wherein the mass ratio of the activated carbon to the mixed solution of hydrogen peroxide-concentrated sulfuric acid is 1:20, and the volume ratio of hydrogen peroxide to concentrated sulfuric acid in the mixed solution of hydrogen peroxide-concentrated sulfuric acid is 1:3;
[0036] S1.2. At room temperature, add activated carbon, tetrapropylammonium hydroxide and pure water into a reactor, stir at a speed of 350 r / min for 3 to 5 hours, filter, wash with pure water, and dry in a drying oven at 75°C for 8 hours to obtain pretreated activated carbon, wherein the mass ratio of activated carbon, tetrapropylammonium hydroxide and pure water is 10:1:70;
[0037] S1.3. At 100°C, mix 20 parts of pretreated activated carbon, 20 parts of surface hydroxylated activated carbon and 60 parts of graphene oxide dispersion, keep warm and stir at 300 r / min for 60 hours, filter, dry at 85°C for 8 hours, and then ball mill at 300 r / min for 4 hours. Pass through a 200-mesh sieve to obtain modified activated carbon. The mass concentration of the graphene oxide dispersion is 3%.
[0038] Preparation of composite flocculant:
[0039] The lignin was dried in a drying oven at 70°C for 6 hours, and then ball-milled at a speed of 400 r / min for 1 hour by a ball mill. 30 parts of the ball-milled lignin, 50 parts by weight of polyacrylamide and 70 parts of pure water were mixed and heated to 80°C, stirred for 1 hour, and dried at 85°C for 7 hours to obtain the composite flocculant.
[0040] Preparation of high-efficiency modified cation exchange resin:
[0041] S1. Rinse 100 parts of cation exchange resin with ethanol, place in a hydrochloric acid solution with a molar concentration of 1 mol / L after drying, react at room temperature for 2 hours, wash with deionized water until neutral, filter and dry to obtain a pretreated cation exchange resin, wherein the mass ratio of the hydrochloric acid solution to the cation exchange resin is 10:1;
[0042] S2, adding the pretreated cation exchange resin, 10 parts of lignin, and 10 parts of the composite flocculant into an organic solvent by weight, heating to 35°C, mixing and stirring at a speed of 300 r / min for 3 hours, filtering, and drying at 50°C for 6 hours to obtain a modified cation exchange resin powder;
[0043] S3. Mix the modified cation exchange resin powder and 10 parts of modified activated carbon, stir evenly at a speed of 350 r / min, and granulate to obtain the modified cation exchange resin.
[0044] Example 2
[0045] Preparation of modified activated carbon:
[0046] S1.1, mixing activated carbon with a mixed solution of hydrogen peroxide and concentrated sulfuric acid, heating to 60°C and stirring for 35 hours, filtering after the stirring, washing the obtained solid with deionized water and ethanol for 2.5 times respectively, and drying at 95°C for 18 hours under vacuum conditions to obtain surface hydroxylated activated carbon, wherein the mass ratio of the activated carbon to the mixed solution of hydrogen peroxide-concentrated sulfuric acid is 2:25, and the volume ratio of hydrogen peroxide to concentrated sulfuric acid in the mixed solution of hydrogen peroxide-concentrated sulfuric acid is 1:4;
[0047] S1.2, at room temperature, add activated carbon, tetrapropylammonium hydroxide and pure water into a reactor, stir at a speed of 350r / min for 3 to 5h, filter, wash with pure water, and dry in a drying oven at 80°C for 10h to obtain pretreated activated carbon, wherein the mass ratio of activated carbon, tetrapropylammonium hydroxide and pure water is 10:2:70;
[0048] S1.3. At 110°C, mix 25 parts of pretreated activated carbon, 25 parts of surface hydroxylated activated carbon and 70 parts of graphene oxide dispersion, keep warm and stir at 300 r / min for 65 hours, filter, dry at 85°C for 10 hours, and then ball mill at 300 r / min for 4 hours. Pass through a 200-mesh sieve to obtain modified activated carbon. The mass concentration of the graphene oxide dispersion is 4%.
[0049] Preparation of composite flocculant:
[0050] The lignin was dried in a drying oven at 70°C for 10 hours, and then ball-milled at a speed of 400 r / min for 2 hours in a ball mill. 35 parts of the ball-milled lignin, 60 parts by weight of polyacrylamide and 75 parts of pure water were mixed and heated to 85°C, stirred for 1.5 hours, and dried at 88°C for 8 hours to obtain the composite flocculant.
[0051] Preparation of high-efficiency modified cation exchange resin:
[0052] S1. Rinse 110 parts of cation exchange resin with ethanol, place in a hydrochloric acid solution with a molar concentration of 2 mol / L after drying, react at room temperature for 3 hours, wash with deionized water until neutral, filter and dry to obtain a pretreated cation exchange resin, wherein the mass ratio of the hydrochloric acid solution to the cation exchange resin is 10:1;
[0053] S2, adding the pretreated cation exchange resin, 13 parts of lignin, and 13 parts of the composite flocculant to an organic solvent by weight, heating to 38°C, mixing and stirring at a speed of 300 r / min for 4 hours, filtering, and drying at 55°C for 7 hours to obtain a modified cation exchange resin powder;
[0054] S3. Mix the modified cation exchange resin powder and 13 parts of modified activated carbon, stir evenly at a speed of 350 r / min, and granulate to obtain the modified cation exchange resin.
[0055] Example 3
[0056] Preparation of modified activated carbon:
[0057] S1.1, mixing activated carbon with a mixed solution of hydrogen peroxide and concentrated sulfuric acid, heating to 80°C and stirring for 48 hours, filtering after the stirring, washing the obtained solid with deionized water and ethanol for 3 times respectively, and drying at 95°C for 20 hours under vacuum conditions to obtain surface hydroxylated activated carbon, wherein the mass ratio of the activated carbon to the mixed solution of hydrogen peroxide-concentrated sulfuric acid is 3:30, and the volume ratio of hydrogen peroxide to concentrated sulfuric acid in the mixed solution of hydrogen peroxide-concentrated sulfuric acid is 1:3;
[0058] S1.2. At room temperature, activated carbon, tetrapropylammonium hydroxide and pure water are added to a reactor, stirred at a speed of 350 r / min for 3 to 5 hours, filtered, washed with pure water, and dried in a drying oven at 85°C for 14 hours to obtain pretreated activated carbon, wherein the mass ratio of the activated carbon, tetrapropylammonium hydroxide and pure water is 10:3:70;
[0059] S1.3. At 120°C, 30 parts of pretreated activated carbon, 30 parts of surface hydroxylated activated carbon and 80 parts of graphene oxide dispersion were mixed evenly, stirred at a speed of 300 r / min for 70 hours, filtered, dried at 85°C for 12 hours, and then ball milled at a speed of 300 r / min for 4 hours in a ball mill, and passed through a 200-mesh sieve to obtain modified activated carbon. The mass concentration of the graphene oxide dispersion is 5%.
[0060] Preparation of composite flocculant:
[0061] The lignin was dried in a drying oven at 70°C for 12 hours, and then ball-milled at a speed of 400 r / min for 3 hours in a ball mill. 40 parts of the ball-milled lignin, 70 parts of polyacrylamide and 85 parts of pure water were mixed and heated to 95°C, stirred for 2 hours, and dried at 90°C for 10 hours to obtain the composite flocculant.
[0062] Preparation of high-efficiency modified cation exchange resin:
[0063] S1. Rinse 120 parts of cation exchange resin with ethanol, place in a hydrochloric acid solution with a molar concentration of 3 mol / L after drying, react at room temperature for 4 hours, wash with deionized water until neutral, filter and dry to obtain a pretreated cation exchange resin, wherein the mass ratio of the hydrochloric acid solution to the cation exchange resin is 10:1;
[0064] S2, adding the pretreated cation exchange resin, 15 parts of lignin, and 15 parts of the composite flocculant into an organic solvent by weight, heating to 40°C, mixing and stirring at a speed of 300 r / min for 5 hours, filtering, and drying at 60°C for 8 hours to obtain a modified cation exchange resin powder;
[0065] S3. Mix the modified cation exchange resin powder and 15 parts of modified activated carbon, stir evenly at a speed of 350 r / min, and granulate to obtain the modified cation exchange resin.
[0066] Comparative Example 1
[0067] The difference between Comparative Example 1 and Example 1 is that the modified activated carbon preparation process in Comparative Example 1 does not undergo step S1.2, and the remaining operations are the same.
[0068] Comparative Example 2
[0069] The difference between Comparative Example 2 and Example 1 is that graphene oxide is not added during the preparation of the modified activated carbon in Comparative Example 2, and the other operations are the same.
[0070] Comparative Example 3
[0071] The difference between Comparative Example 3 and Example 1 is that the activated carbon in Comparative Example 3 is not subjected to any treatment, and the other operations are the same.
[0072] Comparative Example 4
[0073] The difference between Comparative Example 4 and Example 1 is that no lignin is added to the composite flocculant in Comparative Example 4, and the other operations are the same.
[0074] Performance Test:
[0075] The roundness after grinding: According to GB / T 12598-2001 standard, the test results are as follows:
[0076]
[0077] According to the above data, the cation exchange resin prepared by the present invention has a large ion exchange capacity, strong adsorption and regeneration ability, and therefore has good stability and high durability.
[0078] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A highly efficient modified cation exchange resin, characterized in that: The invention comprises the following components in parts by weight: 100 to 120 parts of cation exchange resin, 10 to 15 parts of lignin, 10 to 15 parts of composite flocculant and 10 to 15 parts of modified activated carbon. The preparation process of the modified activated carbon is as follows: S1.1, mixing activated carbon with a mixed solution of hydrogen peroxide and concentrated sulfuric acid, heating to 50-80°C and stirring for 24-48 hours, filtering after stirring, washing the obtained solid with deionized water and ethanol for 2-3 times, respectively, and drying at 95°C for 16-20 hours under vacuum conditions to obtain surface hydroxylated activated carbon, wherein the mass ratio of the activated carbon to the mixed solution of hydrogen peroxide-concentrated sulfuric acid is (1-3): (20-30); S1.2, at room temperature, add activated carbon, tetrapropylammonium hydroxide and pure water into a reactor, stir at a speed of 350r / min for 3 to 5h, filter, wash with pure water, and dry in a drying oven at 75 to 85°C for 8 to 14h to obtain pretreated activated carbon; S1.
3. At 100-120°C, mix 20-30 parts of pretreated activated carbon, 20-30 parts of surface hydroxylated activated carbon and 60-80 parts of graphene oxide dispersion, stir at 300 r / min for 60-70 h, filter, dry at 85°C for 8-12 h, ball mill at 300 r / min for 4 h, and pass through a 200-mesh sieve to obtain modified activated carbon.
2. The high-efficiency modified cation exchange resin according to claim 1, characterized in that The preparation process of the composite flocculant is as follows: The lignin is dried in a drying oven at 70°C for 6 to 12 hours, and then ball-milled at a speed of 400 r / min for 1 to 3 hours by a ball mill, 30 to 40 parts of the ball-milled lignin, 50 to 70 parts of polyacrylamide and 70 to 85 parts of pure water are mixed, and the mixture is heated to 80 to 95°C, stirred at this temperature for 1 to 2 hours, and dried at 85 to 90°C for 7 to 10 hours to obtain the composite flocculant.
3. The high-efficiency modified cation exchange resin according to claim 1, characterized in that In step S1.1, the volume ratio of hydrogen peroxide to concentrated sulfuric acid in the hydrogen peroxide-concentrated sulfuric acid mixed solution is 1:(3-5).
4. The high-efficiency modified cation exchange resin according to claim 1, characterized in that In step S1.2, the mass ratio of the activated carbon, tetrapropylammonium hydroxide and pure water is 10:(1-3):
70.
5. The high-efficiency modified cation exchange resin according to claim 1, characterized in that: In step S1.3, the mass concentration of the graphene oxide dispersion is 3-5%.
6. A method for preparing a highly efficient modified cation exchange resin as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Rinse the cation exchange resin with ethanol, place it in an acidic solution after drying, react at room temperature for 2 to 4 hours, wash it with deionized water until it is neutral, filter it, and dry it to obtain a pretreated cation exchange resin; S2, adding the pretreated cation exchange resin, lignin, and composite flocculant to an organic solvent by weight, mixing and stirring evenly under heating conditions, filtering, and drying to obtain a modified cation exchange resin powder; S3. Mix the modified cation exchange resin powder and the modified activated carbon, stir them evenly at a speed of 350 r / min, and granulate them to obtain the modified cation exchange resin.
7. The method for preparing a highly efficient modified cation exchange resin according to claim 6, characterized in that: In step S1, the acidic solution is a hydrochloric acid or sulfuric acid solution with a molar concentration of 1 to 3 mol / L.
8. The method for preparing a highly efficient modified cation exchange resin according to claim 6, wherein: In step S1, the mass ratio of the acidic solution to the cation exchange resin is 10:
1.
9. The method for preparing a highly efficient modified cation exchange resin according to claim 6, characterized in that: In step S2, the heating temperature is 35-40°C, the mixing speed is 300r / min, and the time is 3-5h.
10. The method for preparing a highly efficient modified cation exchange resin according to claim 6, characterized in that: In step S2, the drying condition is 50-60° C. for 6-8 hours.